Data-driven insights into correlation among geophysical setting, topography and seafloor sediments in the Ross Sea, Antarctic - Lemenkova, Polina (Caderno de Geografia, 2020)
Detailed mapping based on the high-resolution grids, such as GEBCO, ETOPO1, GlobSed, EGM-2008 is crucial for various domains of Earth sciences: geophysics, glaciology, Quaternary, sedimentology, geology, environmental science, geomorphology, etc. The study presented a GMT-based scripting techniques of the cartographic data processing aimed at the comparative analysis of the bathymetry, sediment thickness, geologic objects and geophysical settings in the study area based on various datasets. The study area is located in the Ross Sea, Antarctic. The highest values of the sediment thickness over 7,500 m are dominating in the southwest segment of the Ross Sea closer to the Victoria Land, followed by the region over the Ross Ice Shelf with values between 5,500 to 7,000 m (170°-175°W). The increased sediment thickness (2,500 to 3,000 m) was also mapped seen in the region NE off the Sulzberger Bay (70-75°S to 140-155°W), caused by the closeness of the Marie Bird Land ice coasts. A remarkable correlation between the gravity and the topography of the sea-land border in the Marie Bird Land area is well reflected in the coastal line and a set of the higher values in the free-air gravity. On the contrary, negative values (–60 to -80 mGal) are notable along the submarine toughs stretching parallel in the western part of the basin: e.g. the trough stretching in NW-SE direction in the 170°W-175°E, 65°S-68°S, between the 167°W-175°W, 70°S-72°S. Such correlations are clearly visible on the map, indicating geological lineaments and bathymetric depressions correlating with gravity grids. The paper contributes to the regional studies of the Ross Sea, the Antarctic and Polar region, and development of the cartographic technical methodologies by presenting an application of the GMT for thematic mapping.